2021
DOI: 10.1016/j.jbusres.2019.09.027
|View full text |Cite
|
Sign up to set email alerts
|

The importance of functional and emotional content in online consumer reviews for product sales: Evidence from the mobile gaming market

Abstract: Prior research on online consumer reviews (OCRs) has focused more on the volume and valence of all OCRs as a whole and less on their individual contents. This paper investigates the importance of multidimensional OCR contents, in terms of functional and emotional dimensions, in online marketing. Utilizing a rich dataset of four million online postings and weekly sales for 342 mobile games, this study identifies subcategories of functional OCRsproduct quality, product innovativeness, price acceptability, and pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 74 publications
0
14
0
Order By: Relevance
“…This work extended the expectation confirmation model which is derived from the effort accuracy model discussed by. Jang et al (2019) investigates the functional and emotional dimension of online consumer reviews. The review attributes are identified and their related emotional comments are extracted to map and show how the customer opinion changes according to the attributes.…”
Section: Literature Surveymentioning
confidence: 99%
“…This work extended the expectation confirmation model which is derived from the effort accuracy model discussed by. Jang et al (2019) investigates the functional and emotional dimension of online consumer reviews. The review attributes are identified and their related emotional comments are extracted to map and show how the customer opinion changes according to the attributes.…”
Section: Literature Surveymentioning
confidence: 99%
“…As a form of disruptive technology, EVC aligns with characteristics typically associated with disruptive technologies: first, it possesses capabilities that have created new market value, both independently and through the use of existing standards and protocols (Bower & Christensen, 1995; Rao et al, 2006), and second, its mainstream adoption is often nonlinear and, perhaps in this novel case, arguably serendipitously so (Krotov, 2019). While there is a burgeoning field of research pertaining to OCR in a number of different contexts (see, for example, Jang et al, 2019; Mudambi & Schuff, 2010; Schindler & Decker, 2013), little research has examined the emotional tone and word choice of OCR of EVC platforms. Among the most widely adopted EVC is an application named Zoom.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the types of valence, on the one hand, researchers found that platform-related valence affected the trust in the seller (Ba and Pavlou, 2002). On the other hand, researchers found that product-related consumer reviews' valence was significantly associated with mobile game sales (Jang et al, 2019). Additionally, existing empirical evidence from meta-analysis studies suggests that, in general, positive valence is positively associated with product sales, and negative valence is negatively associated with product sales (Floyd et al, 2014;Rosario et al, 2016;You et al, 2015).…”
Section: Direct and Mediating Effectsmentioning
confidence: 99%